Laser surface processing and model studies - Yilbas, Bekir Sami (Materials Forming, Machining and Tribology,, 2013)
This book introduces model studies associated with laser surface processing such as conduction limited heating, surface re-melting, Marangoni flow and its effects on the temperature field, re-melting of multi-layered surfaces, laser shock processing, and practical applications. The book provides insight into the physical processes involved with laser surface heating and phase change in laser irradiated region. It is written for engineers and researchers working on laser surface engineering.